2021
DOI: 10.7717/peerj.11226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation cover and slope on soil erosion in the Eastern Chinese Loess Plateau under different rainfall regimes

Abstract: Soil erosion is a critical environmental problem of the Chinese Loess Plateau (CLP). The effects of vegetation cover on soil erosion reduction under different rainfall types are not well understood especially in the eastern Chinese Loess Plateau (ECLP). In this study, we monitored runoff and sediment yield at the Fengjiagou water and soil conservation station with five types of vegetation cover (arbor trees (ARC), shrubs (SHC), arable (ABC), natural vegetation (NVC), and artificial grass (APC)) and three slope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…43% of the regional total land area and is the dominant vegetation type on the Plateau [ 2 ]. It provides essential ecosystem functions and services such as carbon sequestration, soil and water conservation, and biodiversity [ 3 , 4 ]. Grassland management and restoration are of great ecological and economic significance in the region.…”
Section: Introductionmentioning
confidence: 99%
“…43% of the regional total land area and is the dominant vegetation type on the Plateau [ 2 ]. It provides essential ecosystem functions and services such as carbon sequestration, soil and water conservation, and biodiversity [ 3 , 4 ]. Grassland management and restoration are of great ecological and economic significance in the region.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, researchers could explore the trade-offs between soil erosion and other ecological services at multiple scales, which would be valuable references for effective and sustainable management and policy decisions for minimizing trade-offs and maximizing synergies of ecological services. Land managers in the Hubei government need to optimize the land-use structure, pay attention to sloping land improvement [ 48 ], increase vegetation coverage [ 49 , 50 ], and increase ecological restoration projects in the west of Hubei. Besides, land policymakers should consider the scale effect of soil and water conservation projects when making land-use plans.…”
Section: Discussionmentioning
confidence: 99%
“…Runoff and sediment processes had a great signi cance to the study of soil erosion characteristics, which could express the dynamic results of soil erosion processes, and response the changes of runoff and sediment with rainfall Vegetation like arbors and grasses can signi cantly promote soil physical and chemical properties, and improve water in ltration velocity, nevertheless, different vegetation types had different effects on the reduction of runoff and sediment (Liu et al, 2019a). Sun et al studied the runoff and sediment loss rates of ve vegetation types, they found that the arbor trees type was the optimum for soil and water conservation, the arbors on soil controlling soil and water conservation has been veri ed in various areas (Sun et al, 2021a). Jia et al found that the combined effect of planting grass and shrub could achieve highly e cient runoff and sediment reduction effect (Jia et al, 2020).…”
Section: Improvement Impact Of Different Ecological Restoration Patte...mentioning
confidence: 99%
“…Laminated vegetation community was able to effectively reduce runoff and soil erosion compared with the single species community (Chen et al, 2018). The bene ts of arbor-grass in soil and water conservation can be attributed to a large canopy, surface grass, litter layers and root system (Sun et al, 2021a). Dense canopy was effective in intercepting rainfall, and reduce the runoff, and litter layers can be decomposed into the surface soil and affect soil erosion (Liu et al, 2017).…”
Section: Improvement Impact Of Different Ecological Restoration Patte...mentioning
confidence: 99%